Workshop Peningkatan Kompetensi Pedagogik Guru Bahasa Inggris SMK di DIY - Margana, Margana; Saputro, Eko Prasetyo Nugroho; Katrina Herda, Rozanah; Sulistyowati, Nina; Gita Atibrata, Tyas; Yulia Purwaningrum, Adriani; Sugesti, Nunik (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
This community service program was initiated to address challenges faced by vocational high school teachers in Yogyakarta. The primary issue is the lack of teacher preparedness to implement differentiated learning models in English lessons. Teachers often lack confidence in their ability to design engaging and relevant learning scenarios for students with diverse characteristics. Additionally, there is a tendency among teachers to assess student skills and readiness uniformly, leading to suboptimal delivery of varied activities, materials, and resources that cater to individual learning styles and preferences. To address these challenges, a workshop was organized to enhance teachers' understanding and skills in differentiated English learning. The workshop aimed at improving the pedagogical competence of vocational high school English teachers in Yogyakarta was conducted between May and June 2024, both online and offline. The program included practical experience-sharing sessions, offline workshops, and online mentoring to review teaching modules created by 49 vocational high school teachers. These modules were based on differentiated learning principles tailored to vocational education. The teachers provided positive feedback on the workshop, indicating that they found the facilities and presentation of the material highly beneficial. The success of this workshop, centered on differentiated learning, underscores its impact on enhancing the pedagogical skills of vocational high school English teachers.